THE EFFECTIVENESS OF USING RANDOM TEXT STRATEGY IN TEACHING READING - Rahmawati; Syamsiarna Nappu; Eka Prabawati Rum (FKIP Unismuh Makassar, 2021)
This pre-experimental research aimed at finding out whether or not the use of Random Text Strategy is effective to improve the students’ literal and interpretative reading comprehension at the 7th grade Students of SMPS Ahlu Shuffah Muhammadiyah, Bantaeng Regency, Province of South Sulawesi. The sample of this research was the 7th grade Students of SMPS Ahlu Shuffah Muhammadiyah.The researcher used purposive sampling method because that class was able to fulfill the rules and they had the characteristics that the researcher wants. Hence, the researcher want to overcome the students’ problem in reading and improve their reading skill through the use of random text strategy then the researcher chose the class with the low English learning achievement compared with the others classes especially for their reading skill and find out the effectiveness of this strategy. The findings of this research shown that there is a significant improvement toward the students’ reading comprehension in the post-test compared with the students score in pre-test. The use of random text strategy is effective to improve the students' literal reading comprehension. It based on the result of the students’ reading test in pre-test compared with the students’ reading test result in post-test.